Formation of Cell Membrane Component Domains in Artificial Lipid Bilayer. Issue 1 (December 2017) - Tero, Ryugo; Fukumoto, Kohei; Motegi, Toshinori; Yoshida, Miyu; Niwano, Michio; Hirano-Iwata, Ayumi
Abstract The lipid bilayer environment around membrane proteins strongly affects their structure and functions. Here, we aimed to study the fusion of proteoliposomes (PLs) derived from cultured cells with an artificial lipid bilayer membrane and the distribution of the PL components after the fusion. PLs, which were extracted as a crude membrane fraction from Chinese hamster ovary (CHO) cells, formed isolated domains in a supported lipid bilayer (SLB), comprising phosphatidylcholine (PC), phosphatidylethanolamine (PE), and cholesterol (Chol), after the fusion. Observation with a fluorescence microscope and an atomic force microscope showed that the membrane fusion occurred selectively at microdomains in the PC + PE + Chol-SLB, and that almost all the components of the PL were retained in the domain. PLs derived from human embryonic kidney 293 (HEK) cells also formed isolated domains in the PC + PE + Chol-SLB, but their fusion kinetics was different from that of the CHO-PLs. We attempted to explain the mechanism of the PL-SLB fusion and the difference between CHO- and HEK-PLs, based on a kinetic model. The domains that contained the whole cell membrane components provided environments similar to that of natural cell membranes, and were thus effective for studying membrane proteins using artificial lipid bilayer membranes.